Descriptors for durian (Durio zibethinus Murr.) - Bioversity International (Bioversity International, 2007)
Descriptors for durian (Durio zibethinus Murr.) were developed by Drs Songpol Somsri, Alfredo T. Corpuz, Salma Idris and Bhag Mal. Dr Bhag Mal coordinated the development of this descriptor list. A draft version prepared in the internationally accepted Bioversity format for descriptor lists was subsequently sent to a number of international experts for their comments and amendments. A full list of the names and addresses of those involved is given in 'Contributors'. Bioversity encourages the collection of data for all five types of descriptors (see Definitions and Use of Descriptors), whereby data from the first four categories - Passport, Management, Environment and Site and Characterization - should be available for any accession. The number of descriptors selected in each of the categories will depend on the crop and the importance of the crop's description. Descriptors listed under Evaluation allow for a more extensive description of accession, but generally require replicated trials over a period of time. Although the suggested coding should not be regarded as the definitive scheme, this format represents an important tool for a standardized characterization system and it is promoted by Bioversity throughout the world. This descriptor list provides an international format and thereby produces a universally understood 'language' for plant genetic resources data. The adoption of this scheme for data encoding, or at least the production of a transformation method to convert other schemes to the Bioversity format, will produce a rapid, reliable and efficient means for information storage, retrieval and communication, and will assist with the utilization of germplasm. It is recommended, therefore, that information should be produced by closely following the descriptor list with regard to ordering and numbering descriptors, using the descriptors specified, and using the descriptor states recommended. This descriptor list is intended to be comprehensive for the descriptors that it contains. This approach assists with the standardization of descriptor definitions. Bioversity does not, however, assumes that each curator will characterize accessions of their collection utilizing all descriptors given. Descriptors should be used when they are useful to the curator for the management and maintenance of the collection and/or to the users of the plant genetic resources. However, highly discriminating descriptors are highlighted in the text to facilitate selection of descriptors.